2021
DOI: 10.1097/nne.0000000000000969
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Resilience, and Related Factors of Nursing Students During the COVID-19 Pandemic

Abstract: Background: COVID-19 and the associated measures to mitigate the spread of the virus have significantly disrupted nursing education.Purpose: The purpose of this study was to examine the relationship between quality of life (QoL), resilience, and associated factors among nursing students during the unprecedented COVID-19 pandemic and subsequent social distancing requirements. Methods: A cross-sectional study using an anonymous survey with nursing students (n = 152) was conducted at a public university in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
72
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 30 publications
13
72
0
6
Order By: Relevance
“…For example, a Polish study found that social distancing, self-isolation and limited access to public spaces among young university students were associated with decreased QoL [ 46 ]. Moreover, a study of nursing students in rural Appalachia, West Virginia, USA, suggested that factors such as resilience and preparedness for online learning were associated with QoL [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a Polish study found that social distancing, self-isolation and limited access to public spaces among young university students were associated with decreased QoL [ 46 ]. Moreover, a study of nursing students in rural Appalachia, West Virginia, USA, suggested that factors such as resilience and preparedness for online learning were associated with QoL [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited numbers of studies that examined the psychological resilience in different samples during the current pandemic. Only one study examining the psychological resilience of nursing students during the COVID‐19 process was found, and 38% of the students in the aforementioned study were found to have poor resilience scores 18 . There are studies that found mean psychological resilience scores as 21.22 ± 4.68 in university students, 38 as 20.47 ± 3.95 adult individuals 39 and as 18.13 ± 5.42 in young adults 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, nursing educators may play an important role by taking advantage of these methods to help students maintain or develop resilience during these challenging times in the COVID‐19 pandemic period. This is because the role of nursing educators is very valuable in terms of developing learning activities or programs to increase resilience, supporting nursing students, providing protection during stressful events, and increasing future employability 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations